2008
DOI: 10.1007/s00531-008-0320-5
|View full text |Cite
|
Sign up to set email alerts
|

The M = 5.1 1980 Arudy earthquake sequence (western Pyrenees, France): a revisited multi-scale integrated seismologic, geomorphologic and tectonic investigation

Abstract: This paper presents a combination of seismic imaging, geomorphologic, and tectonic data and an interpretation of the M = 5.1 1980 Arudy earthquake sequence putting in relation the seismicity, the inherited faults, and the geomorphologic (Würm and postwürm) markers in this region of the Pyrenees. Since the anticlockwise rotation of the regional compression axis in Oligocene time, western Pyrenees are under a dextral regime and the resulting motion is accommodated along major inherited E-W dextral strike-slip fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…[] and Courjault‐Radé et al . [] for the spatial analysis of sets of epicenters using anisotropic wavelets, inspired by a methodology initially developed by Ouillon et al . [, ] for maps of fault or joint traces).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[] and Courjault‐Radé et al . [] for the spatial analysis of sets of epicenters using anisotropic wavelets, inspired by a methodology initially developed by Ouillon et al . [, ] for maps of fault or joint traces).…”
Section: Introductionmentioning
confidence: 99%
“…They thus look more like hidden parameters of the forecasting technique as a whole. Moreover, the use of square cells or isotropic kernels is totally opposite to what could be expected to best approximate a set of plane segments, whose orientations vary in space (see for example Gaillot et al [2002] and Courjault-Radé et al [2009], for the spatial analysis of sets of epicenters using anisotropic wavelets, inspired by a methodology initially developed by Ouillon et al [1996]; Ouillon et al [1995] for maps of fault or joint traces). In some cases, the bandwidth of the kernels may also depend on the size of the local events or on their spatial density: the larger the latter, the finer the resolution.…”
Section: Introductionmentioning
confidence: 99%
“…Using the location of the instrumental seismicity, anisotropic wavelets, structural analysis, or soil gas profiles, some authors have identified some fractures and surface faults possibly related to the Arudy earthquake aftershocks sequence (Darrozes et al, 1998;Gaillot et al, 2002;Baubron et al, 2002;Courjault-Radé et al, 2009). The interpretation of the identified surface faults allows to explain the extensional focal mechanism of some aftershocks in the transpressional regime (σ Hmax oriented NW-SE) generally recognized in this area.…”
Section: The Arudy Epicentral Areamentioning
confidence: 99%
“… Schematic illustration of the horsetail normal faults at the tip of the Jordan Valley Fault (inspired by Courjault‐Radé et al., 2009). Slip type, depth, and thickness data are from Hamiel et al.…”
Section: Discussionmentioning
confidence: 99%